P1-S6.10 Acceptability of Anal Pap self-screening in high-risk women: findings from English and Spanish focus groups in Northern California. (10th July 2011) - McNeil, C; Piñera, C; Maldonado, Y; Levy, V
Abstract : Background: HPV has a causative role in anogenital malignancies. During 2003–2007, the rate of anal cancer for women of all races in California was 2.2/100 000 compared to a national rate of 1.8/100 000. There are no national screening measures for preventing anal cancer, a rare disease that affects more women than men annually. Screening approaches have mainly been studied in men. In preparing for an anal cancer self-screening pilot study in high-risk women, we conducted focus groups in English and Spanish to assess HPV knowledge and acceptability and comprehension of anal Pap instruction materials. Qualitative data regarding acceptability and feasibility of anal pap screening in women have not previously been reported. Methods: Women who were biological females >18 years of age and fluent and literate in English or Spanish were recruited from a public HIV or STD clinic for participation in focus groups conducted by two English and Spanish speaking moderators. Participants were asked a structured list of open ended questions on HPV knowledge, and the acceptability of study forms including an illustrated anal PAP instruction sheet. Qualitative data was collected and reviewed for common themes and emphasis. Results: Two focus groups included 6 English speaking (ES) women and 8 Spanish speaking (SS) women. Knowledge gaps identified for SS women included: basic anatomical terms, HPV can infect both women and men, HPV is a STI, HPV can cause cancer, and the existence of a preventive HPV vaccine. Stigma was identified as an issue associated with STI education for SS women only. Shared knowledge gaps for ES and SS women included: asymptomatic nature of HPV, symptoms potentially caused by HPV, and that warts can turn into cancer. Both groups agreed public health HPV campaigns should target both men and women. Whereas ES women encouraged a more media based approach to HPV education, SS women commented current campaigns are too vague and emphasised a more personal, interactive approach to HPV education in public venues. Self-sampling was viewed positively by participants, along with self-sampling instructions; some modifications to collection materials were suggested. Conclusions: Focus groups revealed significant knowledge gaps in HPV associated malignancies and cancer screening in high-risk females. Anal PAP self-screening appears to be an acceptable approach; however, the large scale implementation of such strategies may require targeted educational campaigns particularly in underserved communities.